Activation of glucocorticoid receptors facilitates ex vivo high-frequency network oscillations in the anterior cingulate cortex - Donaire, Daniel Frías; Demiray, Yunus Emre; Alizade, Ares; Pollali, Evangelia; Albrecht, Anne; Çalişkan, Gürsel (Neuroscience, 2025)
Stress activates the hypothalamic-pituitary-adrenal (HPA) axis, releasing corticosterone (CORT), which binds to glucocorticoid (GR) and mineralocorticoid (MR) receptors in the brain. While stress influences behaviorally relevant network oscillations in limbic regions such as the hippocampus, amygdala, and prefrontal cortex, the direct effects of CORT on these oscillations remain unclear. We examined the acute impact of CORT on anterior cingulate cortex (ACC) oscillations in adult male mice, a hub region for stress and anxiety regulation. Using an ex vivo slice model with cholinergic and glutamatergic activation, we induced beta (10-25 Hz) and slow-gamma (26-45 Hz) oscillations. Our findings show that CORT enhances high-frequency network activity in the ACC in a dose-dependent manner, following an inverted U-shaped dose-response curve, with 1 μM CORT producing significant increases in beta and gamma power. GR activation alone reproduced this effect: the GR agonist dexamethasone mimicked, and the GR antagonist mifepristone blocked, CORT-induced enhancement. MR activation had little effect, and MR antagonism did not prevent the action of CORT. Importantly, acute stress induced by fear conditioning elevated serum CORT levels and enhanced ACC oscillatory activity, with a positive correlation between CORT concentration and oscillation power. Both GR and MR were robustly expressed in the ACC, with expression unaffected by acute stress. These findings highlight the critical role of GR in mediating the effects of CORT on ACC oscillations, which could have implications for understanding neuropsychiatric disorders including anxiety, depression and schizophrenia, where HPA dysfunction, impaired GR signaling, and altered ACC oscillatory activity are commonly observed.
Gesehen am 09.02.2026